The Effectiveness of the Socioscientific Blended Project-Based Learning (PjBL) Model in Improving Higher-Order Thinking Skills - Annur Indra Kusumadani; Lina Agustina; Rina Astuti; Putri Agustina; Harry Affandy (Universitas Veteran Bangun Nusantara Sukoharjo, 2026)
This research aligns with UMS RIP Theme 5 concerning the improvement of education and learning quality. Socioscientific Blended Project-Based Learning (SSI-PjBL) is a learning model that actively engages students through online and face-to-face activities, including reading, discussion, experimentation, data analysis, and problem-solving related to socioscientific issues in society. This study aimed to determine the effectiveness of the SSI-PjBL model in improving the higher-order thinking skills (HOTS) of biology education students at the Faculty of Teacher Training and Education (FKIP) UMS. This study employed a quasi-experimental design involving two groups of 40 students, consisting of an experimental group (20 students) taught using the SSI-PjBL model and a control group (20 students) taught using the conventional Project-Based Learning (PjBL) model. HOTS indicators measured in this study included critical thinking, analysis, evaluation, and problem-solving skills. Data were collected using HOTS-based pretest and posttest essay instruments. Data analysis was conducted using hypothesis testing and effect size analysis. Prior to hypothesis testing, assumption tests including normality and homogeneity tests were performed. Since the data were normally distributed, independent sample t-test was used as a parametric statistical test. The results showed a significant improvement in students’ HOTS in the experimental class compared to the control class. Furthermore, the effect size was calculated using Cohen’s effect size formula and produced a value of 3,190, which was categorized as high according to Cohen’s criteria. These findings indicate that the SSI-PjBL model has a strong effect on improving students’ higher-order thinking skills and can be considered an effective learning approach to support 21st-century biology education.